A new genus and three new species of Anthocephaliidae (Cestoda, Rhinebothriidea) from the round fantail stingray, Taeniurops grabata (Chondrichthyes, Dasyatidae) from the Mediterranean Sea and Atlantic Ocean. (2020) - Boudaya, L.; Neifar, L.; Euzet, L.
Abstract: The spiral intestines of a total of 16 round fantail stingrays Taeniurops grabata from the Mediterranean Sea off Tunisia were examined for cestodes. A new genus is erected in the Anthocephaliidae (Rhinebothridea) as Alveobothrium gen. n., with Alveobothrium grabatum sp. n. as its type species; the new genus differs from the other genera in the order in that its members possess bothridia with an apical sucker, marginal loculi and multiple staggered rows of facial loculi. Alveobothrium zarzisense sp. n. is also described. The species differ in the number of marginal loculi and in proglotid anatomy. Another anthocephaliid belonging to the genus Anthocephalum is also described from T. grabata. Anthocephalum jeancadenati sp. n. is most similar to A. alicae and A. michaeli, but differs in size of terminal proglottid and number of proglottids. All these new species are also found in formalin-preserved cestodes from T. grabata collected at Gorée Island (Senegal) between 1946 and 1954 by the French ichthyologist J. Cadenat and conserved in the personal collection of the late L. Euzet. The presence of the same rhinebothriideans species parasitizing T. grabata in both the Mediterranean (Tunisia) and the eastern Atlantic (Senegal) is discussed.